Implementation of Loose Part Media to Increase Creativity in Early Childhood - Kaenah, Kaenah; Yulia Utami, Sri; Muawwanah, Uyu; Moha, Luqman (Universitas Islam negeri Mahmud Yunus Batusangkar, 2022)
In the learning process, children's liking and knowledge are the main factors in learning that can improve development in children, dislike and ignorance are also inhibiting factors in the learning process and aspects of development in children. Through games with loose part media that have been arranged according to their age group to develop early childhood creativity. However, there are some preschools and level schools that still use LKA or magazine books, so children don't like it and seem monotonous. The author uses a qualitative type of research type of descriptive-qualitative research, with the subject of the study being early childhood. The results of loose part media game research can increase children's liking and curiosity in learning, so as to increase the idea of imagination, creativity, ease of children to understand, and freedom. So that learning that was previously monotonous and boring becomes more fun for children.┬á